AN INVESTIGATION INTO THE USING OF COMPUTER ASSISTED LANGUAGE LEARNING IN ENGLISH LANGUAGE TEACHING - Miyarti Miyarti; Iin Inawati; Bambang Widi Pratolo (IKIP Siliwangi, 2024)
In the era of globalization, the use of technology in daily life has increased significantly. Along with the advancement of technology, one of the new learning tools that have been created known as CALL (Computer Assisted Language Learning) which purposed to make English teaching learning activity more effective and efficient. This research is aimed to review the major theme that be focus from the use of Computer Assisted Language Learning (CALL) in English Learning Teaching classroom. This systematic review was conducted in the fourth phase: collecting, identifying, screening, and reviewing. The research articles that were reviewed in this study fulfilled three criterias: a) research about the use of CALL in ELT, b) peer-reviewed studies, c) taken from reputable journal websites. The search of the journal was conducted using some search engine database such Google Scholar, and reputable journal website finds in Science and Technology Index (Sinta) Website by Kemendikbud. The research’s finding shows that the use of various CALLs application in English teaching learning increases pupil’s English proficiency and improves the effectiveness of the learning process.